University jubilees and university history writing: a challenging relationship: Szerkesztette Pieter Dhondt (Leiden–Boston, Brill, 2014, 257 lap - Bitskey, István (Gerundium, 2017)
University jubilees and university history writing: a challenging relationship -  recenzió